Anarchy = 0 as a Universal Structural Constant: Evidence from Astronomical Observation - Hamidi, Nabil (My University, 2025)
This work examines the hypothesis that Anarchy = 0 describes a universal boundary condition of spacetime: namely, that the universe lacks a single global organizing center or controlling potential. Using observational data (Hubble Top 100 images), I analyze the large-scale distribution of matter — galaxies, clusters, filaments, and voids — to test whether cosmic structure requires central coordination. The data show that structure formation is governed entirely by local interactions: gravitational collapse in dark-matter halos, baryonic cooling, star formation feedback, and large-scale expansion driven by ΛCDM cosmology. In this framework, “Anarchy = 0” means that the universe contains no preferred central frame, no universal potential well, and no top-down control parameter. Instead, order arises from self-organization under field equations (Einstein’s equations for spacetime curvature, Newtonian/relativistic gravity on smaller scales, and thermodynamic/quantum processes). Despite the absence of a central controlling entity, the system exhibits statistical regularity — power-law clustering, hierarchical structure growth, and cosmic web formation — consistent with simulations and observations. Thus, Anarchy = 0 can be interpreted as a statement about the architecture of physical law: the universe operates through uniform local rules applied everywhere, with no global “sovereign” point. Everything observed — from star formation to galaxy clustering — results from distributed dynamics within spacetime, not centralized direction. Further work can test whether this interpretation is quantifiable across scales and whether it constitutes a measurable cosmological invariant.